Criminología forense: concepto y aplicaciones en el sistema de justicia penal - Camacho Espinosa, Gregorio Javier (Archivos de criminología, seguridad privada y criminalística, 2023)
This article exposes the state of the art in relation to forensic criminology. Addressing two basic issues: on the one hand, the concept of it starting from definitions from other countries, to those that have been elaborated in Mexico and on the other, the possible applications that this science can have particularly in the criminal justice system, from criminal profiling, violence risk assessment and linkage analysis, up to the psychological autopsy and victim risk or exposure assessment.